Implicações do reenquadramento semântico-discursivo das circunstâncias expressas pelos sintagmas adverbiais para o ensino médio. - Assad Alvares , Claudia (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This paper reports a research project whose aims are: to describe Azeredo´s proposal to reframe adverbial sbordinated clauses semantically and to analyse it by comparing his suggestions to others by authors such as Carone (1988, 1991), Castillo (2012) anda Neves (1999); to analyse semantics proprierties of adverbial phrases and it´s differents nuances in a select corpus (ten textbooks, ten journalistics texts being five from newspapers and five from magazines, and five movies scripts connected with the theme of rare diseasses and, finally, to discuss those tehoretical alternatives and analisis to college students on Morphosyntax classes.
Keywords: Portuguese teaching; Morphosyntax; Adverbial phrase; Semantic and discoursive reframe